Characterisation of GABAergic interneurons in a dual-hit neurodevelopmental model for schizophrenia - Cale, Jennifer (2023)
Schizophrenia is a debilitating mental illness distinguished by positive, negative, and cognitive symptoms. Pathogenesis begins in early neurodevelopment and leads to excitatory-inhibitory imbalance that is poorly managed by current treatments. Preclinical models used to understand the disease and evaluate novel therapeutics should therefore consider GABAergic deficits. One approach to improve preclinical models' face, construct, and predictive validity incorporates dual neurodevelopmental ‘hits’. For example, ‘PCP-Iso’ rats that undergo neonatal administration of phencyclidine, to disrupt the development of glutamatergic circuitry, and then post-weaning isolation, to mimic adolescent social stress, exhibit more significant behavioural deficits than either of the single hit models. PCP-Iso may also have better predictive validity than their single-hit counterparts.